Prospective natural history study of C9orf72 ALS clinical characteristics and biomarkers. (22nd October 2019) - Cammack, Alexander J.; Atassi, Nazem; Hyman, Theodore; van den Berg, Leonard H.; Harms, Matthew; Baloh, Robert H.; Brown, Robert H.; van Es, Michael A.; Veldink, Jan H.; de Vries, Balint S.; Rothstein, Jeffrey D.; Drain, Caroline; et al.
Abstract : Objective: To define the natural history of the C9orf72 amyotrophic lateral sclerosis (C9ALS) patient population, develop disease biomarkers, and characterize patient pathologies. Methods: We prospectively collected clinical and demographic data from 116 symptomatic C9ALS and 12 non–amyotrophic lateral sclerosis (ALS) full expansion carriers across 7 institutions in the United States and the Netherlands. In addition, we collected blood samples for DNA repeat size assessment, CSF samples for biomarker identification, and autopsy samples for dipeptide repeat protein (DPR) size determination. Finally, we collected retrospective clinical data via chart review from 208 individuals with C9ALS and 450 individuals with singleton ALS. Results: The mean age at onset in the symptomatic prospective cohort was 57.9 ± 8.3 years, and median duration of survival after onset was 36.9 months. The monthly change was −1.8 ± 1.7 for ALS Functional Rating Scale–Revised and −1.4% ± 3.24% of predicted for slow vital capacity. In blood DNA, we found that G4 C2 repeat size correlates positively with age. In CSF, we observed that concentrations of poly(GP) negatively correlate with DNA expansion size but do not correlate with measures of disease progression. Finally, we found that size of poly(GP) dipeptides in the brain can reach large sizes similar to that of their DNA repeat derivatives. Conclusions: We present a thorough investigation of C9ALS natural history, providing the basis for C9ALS clinical trial design. We found that clinical features of this genetic subset are less variant than in singleton ALS. In addition, we identified important correlations of C9ALS patient pathologies with clinical and demographic data.